Antibacterial and anti-cancer activities of Artemisia turcomanica extract on gastric cancer cell line (AGS) and its interaction on cyclin D1 and cyckin E genes - Nooshin Fathi; Farzaneh Tafvizi; Amir Mirzaie (Institue of Medicinal Plants, ACECR, 2020)
Background: The use of medicinal herbs in traditional medicine has been important and many of these plants have antioxidant, anti-inflammatory, antimicrobial and anti-cancer effects. Objective: The aim of this study was to evaluate the antibacterial and anti-cancer effects of Artemisia turcomanica extract on gastric cancer cell line (AGS) and its effect on expression of cyclin D1 and cyclin E genes. Methods: At first the alcoholic extract of A. turcomanica was prepared and its antibacterial effect was evaluated using MIC (Minimum Inhibitory Concentration) method. Subsequently, the cytotoxic effect of extract on AGS cell line was studied using MTT method after 24, 48 and 72 hours. Moreover, the apoptotic effect of extract was determined via annexin FITC-V and PI staining. Finally, the gene expression of cyclin D1 and cyclin E were measured using Real Time PCR method. Results: The antibacterial results show that the A. turcomanica extract had significant effect on Escherichia coli. In addition, the results of MTT assay indicated that the maximum cytotoxic effect of A. turcomanica extract was observed in 24 h and over time, its cytotoxic effects were decreased. The maximum apoptotic effect and minimum necrosis effects was observed in 48 h. Also, the Real Time PCR results reveal that the gene expression of cyclin D1 and cyclin E1 was down-regulated. Conclusion: The results of this study show that the A. turcomanica extract had cytotoxic and apoptotic effects on AGS cell line and it can be used as anticancer candidate in cancer therapy and prevention after further studies.